Pengaruh Penambahan L-Arginin terhadap Total Spermatozoa Motil (TSM) pada Semen Beku Kambing Boer - Fahlevi, Reza; Yunita, Citra Nurma; Pradana, Devi Kusuma; Dewi, Sari; Falah, Reo Radius (AgriMalS, 2025)
One important factor determining this quality is the dilution process, which aims to maintain sperm motility and viability during the freezing process. Low storage temperatures can causecold shock, namely damage to the plasma membrane of cells which can cause the death of spermatozoa.This study aims to evaluateThe effect of adding L-Arginine on total motile spermatozoa (TSM)in frozen Boer goat semen. The fresh semen used had a minimum individual motility of 80% and a mass motility of ++. The diluent used was Tris-aminomethane egg yolk, with varying concentrations of L-Arginine.Fresh semen is evaluated macroscopically based oncolor, odor, volume, consistency, and pH, then continued with observation of total motile spermatozoa after the freezing process to assess the effect of adding L-Arginine.This research usesCompletely Randomized Design (RAL)with 4 treatments and 10 replications, namely:P0: 0 mM L-Arginine (control), P1: 5 mM L-Arginine, P2: 6 mM L-Arginine P3: 7 mM L-Arginine. The results of this study: The average percentage of Total Motile Spermatozoa (TSM) after freezing is:P2 (6 mM): 28,25 ± 2,38%, P0 (0mM): 25,00 ± 2,38%, P3 (7 mM): 24,15 ± 2,38%, P1 (5 mM): 23,20 ± 2,62%. Addition L-Arginine 6 mM (P2) provided the best results in increasing the total percentage of motile spermatozoa after freezing. Thus, a concentration of 6 mM L-Arginine can be recommended as the optimal.